An integrated approach to the determination and consequences of residual stress on the fatigue performance of welded aircraft structures - Edwards, Lyndon; Fitzpatrick, Michael E.; Irving, Phil E.; Sinclair, I.; Zhang, Xiang; Yapp, David (Cranfield University, 2006)
Although residual stress in welded structures and components has long been known to have an effect on their fatigue performance, access to reliable, spatially accurate residual stress field data has been limited. Recent advances in neutron and synchrotron X-ray diffraction allow a far more detailed picture of weld residual stress fields to be obtained that permits the development and use of predictive models that can be used for accurate design against fatigue in aircraft structures. This paper describes a fully integrated study of the three- dimensional residual stress distribution accompanying state-of-the-art fusion welds in 2024-T4 aluminum alloy, and how it is affected by subsequent machining and service loading. A particular feature of this work has been the development of techniques allowing the nondestructive evaluation of the residual stress field in the full range of specimens used to provide the design data required for welded aircraft structures and the integration of this information into all aspects of damage tolerant design.
Keywords: residual stresses; fatigue; damage tolerance; structural integrity; welded aircraft structures